Ion-pairing reagent-free hydrophilic interaction LC-MS/MS method for therapeutic drug monitoring of amikacin in neonates - Saikumar Matcha, Bhim Bahadur Chaudhari, Surulivelrajan Mallayasamy, Leslie E Lewis,Sudheer Moorkoth (Journal of Applied Pharmaceutical Science, 2023)
Amikacin, is a first-line antibiotic frequently used in the neonatal intensive care unit. It exhibits changed pharmacokinetic behavior with physiological and clinical conditions such as hypothermia, leading to nephrotoxicity in neonates. Therefore, clinical laboratories require a practically adaptable analytical method to monitor amikacin regularly and to conduct pharmacokinetic studies. Currently available analytical methods for amikacin employ tedious, time-consuming, and non-reproducible derivatization techniques and ion pairing reagents. With the use of mixed mode hydrophilic interaction ion-exchange LC-MS/MS, a sensitive analytical method that avoids the time-consuming derivatization step and the ion suppression caused by the ion-pairing reagent has been validated, including clinical sample analysis. The separation was achieved on a polymer-based HILICpakVC-50 2D (150 X 2.1) mm, 5 μm column using a mobile phase consisting of acetonitrile and ammonia solution with gradient programming. The method involved simple protein precipitation with chilled acetonitrile followed by water-based extraction to achieve the highest possible recovery from a 50 μL plasma aliquot. The method is linear in the 0.5 to 100 μg/mL range, with a regression coefficient of 0.99843. The accuracy and precision of the method were within acceptable limits and had an overall recovery of 97.32 % and 98.39 % at LQC and HQC, respectively.
Keywords: Amikacin, Aminoglycoside, Therapeutic Drug Monitoring, LC-MS/MS, Neonates